Aerobic exercise modulates cytokine profile and sleep quality in elderly - Abd El-Kader, Shehab M; Al-Jiffri, Osama H (African health sciences, 2019)
Background: Sleep disturbance is a major problem for older adults which can be exacerbated by increased inflammation as aging is associated with increased circulating pro-inflammatory and lower anti-inflammatory cytokines. There is a need to develop alternative medicine techniques to help improve sleep quality in the elderly. Objective: To investigate the effects of aerobic exercise training on the sleep quality and inflammatory cytokines in elderly subjects. Material and methods: Forty previously sedentary elderly subjects participated in this study, their age ranged from 61- 67 years. All subjects were randomly assigned to supervised aerobic exercise intervention group (group A, n=25) or control group (group B, n=25). Polysomnographic recordings for sleep quality assessment, interleukin- 6 (IL-6), tumor necrosis factor- alpha (TNF-α) and interleukin-10 (IL-10) were measured before and after 6 months at the end of the study. Results: There was a significant increase in total sleep duration, sleep efficiency and sleep onset latency in group(A) after 6 months of aerobic exercise training, while, wake time after sleep onset and rapid eye movement (REM) latency significantly reduced after 6 months of aerobic training compared with values obtained prior to aerobic exercise training. Also, the mean values of TNF- α and IL-6 decreased significantly and the mean value of IL-10 significantly increased in group (A) after the aerobic exercise training, however the results of the control group were not significant. Moreover, there were significant differences between both groups at the end of the study. Conclusion: Exercise training can be considered as a non-pharmacological modality for modifying sleep quality and inflammation among elderly. DOI: https://dx.doi.org/10.4314/ahs.v19i2.45 Cite as: Abd El-Kader SM, Al-Jiffri OH. Aerobic exercise modulates cytokine profile and sleep quality in elderly. Afri Health Sci.2019;19(2): 2198-2207. https://dx.doi.org/10.4314/ahs.v19i2.45